Diversidade genômica de Leishmania infantum isolados de cães naturalmente infectados no município de Januária, Minas Gerais, Brasil - Ramon Vieira Nunes (2020)
Canine visceral leishmaniasis (CVL) is a zoonosis commonly caused by Leishmania (Leishmania) infatum, affecting mainly domestic dogs in the urban context. These hosts have intense visceral and cutaneous parasitism, which would facilitate infection of the vectors. Canine enzooty regularly precedes the occurrence of VL in humans. The present research aims to clinically characterize the animals; diagnose CVL; to identify the protozoan species of the genus Leishmania causing CVL and to characterize molecularly isolates obtained from bone marrow aspirates. The study was carried out in the city of Januária, located in the northern region of the State of Minas Gerais, Brazil. Serum samples, spleen fragments, ear skin and bone marrow aspirates were collected from 100 infected animals in two moments and areas: 2017 urban area and 2019 rural area. The diagnosis was confirmed by serology (DPP, RIFI and ELISA) and also by PCR-ITS1 in samples of skin, spleen and bone marrow. For species identification, RFLP was performed on PCR positive samples. Samples of bone marrow aspirates were placed in NNN / LIT culture medium to obtain isolates. DNA from the isolates (n = 27) was extracted, purified, amplified and sequenced. All animals in this study showed clinical signs suggestive of CVL, that the score observed was 2-17 points (0-19), characterizing the sample population as clinically symptomatic and allowing inferences of correlation with antibody titers (RIFI). The diagnostic confirmation of CVL was evidenced in 100% of the dogs, in at least one of the techniques mentioned. By PCR-RFLP, L. (L.) infantum was identified in 72% of the animals, with no other species identified. 27 strains were isolated, of which 20 had the sequenced genomes that were analyzed together with the reference genome of L. infantum (JPCM5). Ploidy alteration were detected regardless of location (urban or rural) and / or temporality (2017 or 2019). All sequenced genomes exhibited polysomy of chromosome 31, as well as urban isolates / 2017 polyploid of chromosome 23. Analyzes of functional enrichment by GO revealed gene enrichments involved in enzymatic processes of conversion of acetate to acetyl-Coa mediated by AceCS for lipid synthesis (Figure 13) and Heme degradation, to limit the production of free radicals in macrophages parasitized. Both ploidy and SNVs (PCA) analyzes revealed the existence of 2 main clusters: 1st) Urban cluster - consisting of all urban genomes isolated in 2017; 2 °) Rural cluster: formed by all isolated rural strains in 2019. Analysis of SNVs showed between 814 and 987 variants in each genome and 99.99% identity among the 20 genomes. In short, the 2 main clusters formed were characterized by temporality or year of collection of clinical specimens (2017 and 2019) and / or geographic location (urban and rural), with the first cluster, urbano / 2017 and the second rural / 2019, suggesting spatial and / or temporal interferences in the genomic evolutionary processes of this organism.